APA RESPONS DAN HARAPAN SISWA SMA TENTANG BLENDED LEARNING? - I Made Kirna; Ida Bagus Nyoman Sudria; I Made Tegeh (Universitas Pendidikan Ganesha, 2015)
Abstracts: What are Responses and Expectations of Senior High School Students to Blended Learning? The effectiveness of learning innovation could not ignore an important aspect of student’s characteristics. The purposes of this research were to (1) describe the response of high school (SMA) students towards learning chemistry delivered by blended learning (BL), and (2) to explore the expectations of students towards the online content and chemistry learning management deli-vered by BL. To obtain the responses and the expectations of students, 140 questionnaires distri-buted online to the grade nine of class XI MIA SMA students (respondents) in seven SMAin seven-regencies in Bali: SMAN 1 Gianyar, SMAN 1 Sidemen Karangasem, SMAN 2 Semarapura, SMAN 5 Denpasar, SMAN 1 Singaraja, SMAN 1 Kuta Utara, and SMAN 1 Kediri Tabanan. The result of the research shows that only 110 respondentscompleted a questionnaire of students responsesabout BL and 106 respondents completed questionnaires of students’ expectations towards online content and management of BL. SMA students gave a positive response to the application of BL and provi-ded important inputs which were useful fordeveloping online content and management of BL for se-nior high school students.Key Words: blended learning, chemistry instruction, online contentAbstrak: Apa Respons dan Harapan Siswa SMA tentang Blended Learning? Efektivitas suatu inovasi pembelajaran tidak bisa mengabaikan aspek penting karakteristik siswa. Tujuan penelitian ini adalah untuk (1) mendeskripsikan respons siswa SMA terhadap pembelajaran kimia yang di-sampaikan secara blended learning (BL), dan (2) menjaring harapan siswa terhadap konten dan pe-ngelolaan pembelajaran kimia yang disampaikan secara BL. Untuk memperoleh gambaran tentang respons dan harapan siswa tersebut, 140 angket disebarkan secara online ke siswa SMA kelas XI MIA yang tersebar di 7 SMA di 7 kabupaten/kodya di Bali, yaitu SMAN 1 Gianyar, SMAN 1 Side-men Karangasem, SMAN 2 Semarapura, SMAN 5 Denpasar, SMAN 1 Singaraja, SMAN 1 Kuta Utara, dan SMAN 1 Kediri Tabanan. Hasil penelitian menunjukkan bahwa hanya 110 siswa yang mengisi angket respos siswa terhadap BL dan 106 responden yang mengisi angket harapan siswa terhadap konten online dan pengelolaan BL. Siswa SMA memberikan respon yang positif terhadap penerapan BL dan memberikan masukan yang berguna untuk mengembangkan konten online dan pengelolaan BL untuk siswa SMA.Kata-kata Kunci: blended learning, konten online, pembelajaran kimia